TO THE QUESTION OF STANDARDIZATION OF THE TARRAGON RAW - N. N. Bakova; O. M. Shevchuk; L. A. Logvinenko; L. A. Timasheva (Овощи России, 2019)
Tarragon (Artemisia dracunculus L.) is a spicy aromatic culture, perspective to use in the food and medical industry. In the collection of aromatic and medicinal plants of the Nikita Botanical Gardens, tarragon is represented by two varieties: Isumrud and Travnevy. The Isumrud variety is characterized by a high content of essential oil (0.6% of the wet weight) of the methylchavicol chemotype (the main component of the essential oil is methylchavicol, whose mass fraction is up to 91%) and is perspective to use not only as a spice, but also in medicine as a reducing facilities. The variety Travnevy contains only 0.1% of the essential oil from the wet mass of the sabineno-elemicin chemotype (the main components of the essential oil are sabinen (40.0%) and trans-from-iso-elemicin – 26.1%), characterized by high productivity of the aerial mass (12 kg/m2 ), the main direction of use in the food industry as a spice. Due to the lack of requirements for dry raw tarragon, we have developed a draft technical specifications for dry crushed tarragon raw materials TS 01.28.30-009-01579640-2018. Specifications apply to dried whole and crushed raw materials, intended for the manufacture of water and water-alcohol infusions, as a source of biologically active substances, as a component for seasonings to meat, fish dishes, for use in cooking, as well as in the production of alcohol and soft drinks. The main physicochemical indicators of whole and crushed tarragon raw materials (type, size, smell, taste, mass fraction of essential oil, impurities, moisture, ash) are presented.